Quantitative mass spectrometry of TATA binding protein-containing complexes and subunit phosphorylations during the cell cycle - Baltissen Marijke PA (Proteome Science, 2009)
Abstract Background Progression through the cell cycle is accompanied by tightly controlled regulation of transcription. On one hand, a subset of genes is expressed in a cell cycle-dependent manner. On the other hand, a general inhibition of transcription occurs during mitosis. Genetic and genome-wide studies suggest cell cycle regulation at the level of transcription initiation by protein complexes containing the common DNA-binding subunit TATA binding protein (TBP). TBP is a key player in regulating transcription by all three nuclear RNA polymerases. It forms at least four distinct protein complexes with TBP-associated factors (TAFs): SL1, B-TFIID, TFIID, and TFIIIB. Some TAFs are known to remain associated with TBP during the cell cycle. Here we analyze all TAFs and their phosphorylation status during the cell cycle using a quantitative mass spectrometry approach. Results TBP protein complexes present in human cells at the G2/M and G1/S transitions were analyzed by combining affinity purification with quantitative mass spectrometry using stable isotope labeling with amino acids in cell culture (SILAC). Phosphorylations were mapped and quantified after enrichment of tryptic peptides by titanium dioxide. This revealed that subunit stoichiometries of TBP complexes remained intact, but their relative abundances in nuclear extracts changed during the cell cycle. Several novel phosphorylations were detected on subunits of the TBP complexes TFIID and SL1. G2/M-specific phosphorylations were detected on TAF1, TAF4, TAF7, and TAFI41/TAF1D, and G1/S-specific dephosphorylations were detected on TAF3. Many phosphorylated residues were evolutionary conserved from human to zebrafish and/or drosophila, and were present in conserved regions suggesting important regulatory functions. Conclusions This study provides the first quantitative proteomic analysis of human TBP containing protein complexes at the G2/M and G1/S transitions, and identifies new cell cycle-dependent phosphorylations on TAFs present in their protein complex. We speculate that phosphorylation of complex-specific subunits may be involved in regulating the activities of TBP protein complexes during the cell cycle.